(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2025)
. The topic of the article not accidentally refers to the title of the publishing series “Classics of Polish Modernity”, in which the August Count Cieszkowski Foundation has been publishing for several years the works of significant representatives of Polish thought of the 19th and 20th centuries, with particular emphasis on the current of “religious philosophy” of that period. The text is, on the one hand, an attempt to outline the editorial output and ideas of this series, and, on the other hand, formulates general questions on the historical self-knowledge of Polish thought, particularly philosophical thought, on the basis of this presentation. What is the attitude of contemporary Polish philosophy to its own intellectual heritage? What is the historical specificity of Polish modernity against the background of the European context? Where is the boundary between modernity and contemporaneity in the development of Polish philosophical reflection? And finally: what do we really think about our own classics of philosophy and what do we need them for? Answers to these and other questions will constitute an attempt at a comprehensive discussion of the title issue